How to make dwarf Bougainvillea - Jain, Ritu; Janakiram, T (Indian Horticulture, 2019)
Bougainvillea, a member of family Nyctaginaceae is a vigorously growing evergreen landscape plant which requires minimum maintenance. It is used for many purposes like shrub, climber, standard, topiary, hedge, over arches, pergolas and as potted plant. Due to low water and maintenance requirements, it has become a prominent potted plant in urban and peri-urban areas. Due to its fast growth habit, it needs regular pruning to maintain it as a potted plant by expert gardener. To avoid pruning and to keep it in shape, an alternative method of using growth retardants to induce dwarfing by checking the growth was standardized. Out of different growth retardants and their concentration used, it was observed that paclobutrazol was the most effective retardant when used either in drench or spray form for inducing dwarfing without affecting floriferousness in cv. Mahara and Shubhra.